The effect of span-to-height aspect ratio to the damage index ratio of RC buildings with vertical irregularity setbacks - Taufiq Ilham Maulana,; Muhammad Ibnu Syamsi,; Fanny Monika,; Hakas Prayuda, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Many type irregularities exist in reinforced concrete frame buildings to accommodate the demand from architectural and aesthetic aspects. One of it is vertical irregularity setback. Its appearance affected the building seismic performance and the damage distribution. Previous researchers proposed equations to correlate between irregularity indices and damage index ratio of setback buildings. However, the aspect ratio between span and height were not included in the formula. This research presents the influence of span-to-height ratio to damage index ratio of the reinforced concrete buildings with setbacks. A set of 2D RC frames having setbacks are evaluated with nonlinear dynamic analyses under three seismic input motions. Several span-to-height aspect ratios were applied by changing the inter-story heights. The Park-Ang damage index was adopted to evaluate the damage index ratio between tower part and base part to represent the damage distribution and the inter-story drifts were observed to represent the building seismic performance. The result showed that under the same earthquake motions, the decrease in span-to-height ratio majorly increased the maximum inter-story drifts. The damage index ratio values between tower part and base part fluctuated, however the similar pattern of damage distributions between tower and base structure were obtained.